2013
DOI: 10.5665/sleep.2464
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stressor Predictability on Escape Learning and Sleep in Mice

Abstract: Machida M; Yang L; Wellman LL; Sanford LD. Effects of stressor predictability on escape learning and sleep in mice. SLEEP 2013;36(3):421-430.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 64 publications
2
20
0
Order By: Relevance
“…Others, based on positive correlations of REM amounts with fear recall in human subjects, have suggested that REM sleep deprivation be considered as a means to attenuate fear memory associated with distressing events. 48 We have found that REM can be either increased or decreased in association with specific stressor characteristics or experimental parameters of conditioned fear, 25 but neither increases nor decreases in REM alone are predictive of the expression of fear memory elicited by reexposure to the shock context. 10 However, consistent results of REM increase after controllable stress but not after uncontrollable stress 9,13 and in association with fear extinction in animal model 52 suggest critical roles of post-ST REM in fear regulation.…”
Section: Bla Involvement In Rem Regulationmentioning
confidence: 94%
See 2 more Smart Citations
“…Others, based on positive correlations of REM amounts with fear recall in human subjects, have suggested that REM sleep deprivation be considered as a means to attenuate fear memory associated with distressing events. 48 We have found that REM can be either increased or decreased in association with specific stressor characteristics or experimental parameters of conditioned fear, 25 but neither increases nor decreases in REM alone are predictive of the expression of fear memory elicited by reexposure to the shock context. 10 However, consistent results of REM increase after controllable stress but not after uncontrollable stress 9,13 and in association with fear extinction in animal model 52 suggest critical roles of post-ST REM in fear regulation.…”
Section: Bla Involvement In Rem Regulationmentioning
confidence: 94%
“…Methods for fear conditioning and fear memory testing have been described in Machida et al 25 After baseline recordings were obtained, the mice were connected bilaterally to optic fiber cables and placed in a shock chamber (Coulbourn Instruments) for shock training (ST). DataWave Experimenter's Workbench (Data Wave Technologies, Loveland, CO) was used to control the timing and duration of footshock and light.…”
Section: Peri-shock Inhibition Of Bla In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…Increases in REM sleep were also observed in rabbits after handling, which led to more activity in successive open-field behavior assessment (Denenberg et al 1977). Rodent studies also showed increases in REM sleep episodes after learning in associative fear-related learning tasks, such as the fear-conditioning paradigm and an escapable shock task (Sanford et al 2010;Machida et al 2013;Menz et al 2013). REM sleep also increased in rodents after training in the Morris water maze paradigm Rose 1996, 1997).…”
Section: Sleep Enhances Memory Consolidationmentioning
confidence: 80%
“…Activation of MR increases SWS, while activation of GR by dexamethasone increases wake [Born et al, 1989[Born et al, , 1991. Acute stress, for example, foot shock or immobilization [Machida et al, 2013;Vazquez-Palacios and Velazquez-Moctezuma, 2000], hydrocortisone, [Vazquez-Palacios et al, 2001] or chronic administration of corticosterone [Wang et al, 2014[Wang et al, , 2015 suppresses sleep and alters EEG architecture in animal models.…”
Section: Hpa Axis Hormones and Sleep Interactionsmentioning
confidence: 99%